2019
DOI: 10.2139/ssrn.3381299
|View full text |Cite
|
Sign up to set email alerts
|

Much Ado About Nothing? Online Platform Price Parity Clauses and the EU Booking.com Case

Abstract: Online platforms often impose Price Parity Clauses to prevent sellers from charging lower prices on alternative sales channels. We provide quasi-experimental evidence on the full removal of Price Parity Clauses in France in 2015 and in Italy in 2017 for hotels listed on Booking.com. Our analysis reveals a relatively limited effect in the short run followed by a significant reduction in room prices in the medium run. Moreover, we find that hotels affiliated with chains decreased their prices more than independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The results of this study support previous research [10] which suggested that non-physical services are one of the predictors that can satisfy customers. research [4] shows that price sensitivity influences customers' choice to choose hotels.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study support previous research [10] which suggested that non-physical services are one of the predictors that can satisfy customers. research [4] shows that price sensitivity influences customers' choice to choose hotels.…”
Section: B Discussionmentioning
confidence: 99%
“…Price is the value of money charged and issued by consumers to buy service so that it can be used and feel the benefits after using it [4]. Price serves as a reference in calculating the selling value of a service [5].…”
Section: Introductionmentioning
confidence: 99%
“…, 2021). Thus, platform owners try to hinder this disintermediation by monitoring communication between participants or by implementing best-price clauses that force complementors to charge lower prices nowhere else (Gu and Zhu, 2021; Mantovani et al. , 2019).…”
Section: Implications Of Regulation Like the Dma For Information Systemsmentioning
confidence: 99%
“…Designing and maintaining effective subsidizing strategies is challenging because the non-subsidized market side will try to draw the subsidized side away from the platform (Zhou et al, 2021). Thus, platform owners try to hinder this disintermediation by monitoring communication between participants or by implementing best-price clauses that force complementors to charge lower prices nowhere else (Gu and Zhu, 2021;Mantovani et al, 2019).…”
Section: Implications Of Regulation For Economic Is Digital Platform ...mentioning
confidence: 99%
“…Also, consistent with our model, they do not find any evidence of inflated transaction fees charges by the online travel agents following the imposition of PPCs. Mantovani, Piga, and Reggiani (2019) show that the removal of PPCs in France and Italy had a limited effect on hotel room prices in the short run and a more significant effect in the long run. They find that hotels affiliated with chains decreased their prices more than independent hotels, both in the short and medium runs.…”
Section: Related Literaturementioning
confidence: 99%